2017
DOI: 10.22225/jr.1.2.34.279-297
|View full text |Cite
|
Sign up to set email alerts
|

Prioritas Aspek-Aspek Tipologi Linguistik Pada Pemetaan Masalah-Masalah Kebahasaan

Abstract: Tulisan ini memberikan tinjauan teoretis mengenai kajian tipologi linguistik yang dibedakan dari kajian tipologi bahasa secara struktural yang selama ini lebih akrab di kalangan linguist. Fokus penjabaran teoretis dimaksud adalah penjabaran prinsip-prinsip kerja kajian tipologi linguistik sampai dengan jabaran aspek-aspek tipologi linguistik bahasa Lokal di Indonesia yang diprioritaskan untuk dikaji. Instrumen penjaringan data lapangan, proses identifikasi sampai pemetaan masalah pada aspek ini juga dijabarkan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Researchers would investigate the forms of the registers, define the typology of the registers, and then classify them in phrases or in the form of words after doing research in the traditional Kahayan market and discovering numerous types of registers. According to Umiyati (2015), the overall goal of research on language typology or linguistic typology is to classify languages according to their structural properties, and registers in typology include phrases and clitics. The phrase, according to Eriyanti et al, (2020), is a collection of two or more words that make a meaning; it cannot be separated since the meaning will change.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers would investigate the forms of the registers, define the typology of the registers, and then classify them in phrases or in the form of words after doing research in the traditional Kahayan market and discovering numerous types of registers. According to Umiyati (2015), the overall goal of research on language typology or linguistic typology is to classify languages according to their structural properties, and registers in typology include phrases and clitics. The phrase, according to Eriyanti et al, (2020), is a collection of two or more words that make a meaning; it cannot be separated since the meaning will change.…”
Section: Discussionmentioning
confidence: 99%
“…Itu artinya konstruksi aplikatif instrumental dan lokatif belum dijelaskan dalam penelitiannya. Selain itu, penelitian terkait tipologi bahasa Indonesia juga masih perlu ditelaah dan diprioritaskan (Jufrizal, 2004(Jufrizal, , 2007Umiyati, 2017). Oleh karena itu, peneliti ingin mengidentifikasi dan menginvestigasi konstruksi aplikatif bahasa Indonesia.…”
Section: A Pendahuluanunclassified
“…Thus, the methodologies and results of typological research are basically compatible with any https://jurnal.uisu.ac.id/index.php/languageliteracy 170 Nationally Accredited SINTA 3, and indexed in DOAJ and Copernicus grammatical theory (Jufrizal, 2018). Eventually, language typology is generally intended to classify languages through structural behavior based on the peculiarities of the language (Umiyati, 2015). Some of studies in language typology have been carried out, such as a study on Indonesian Language: A Study of Syntactic Typology by Artawa in 1998 and research entitled Balinese Language: A Study of Syntactic Typology which concluded that the Balinese language exhibits syntactic ergative behavior (Artawa, 1998).…”
Section: Literature Reviewmentioning
confidence: 99%